TINGKAT PENGETAHUAN DAN SIKAP PETANI DI SUBAK SEMPIDI TENTANG SINAR MATAHARI SEBAGAI FAKTOR RISIKO KANKER KULIT - Richard, Richard; Darmaputra, I Gusti Nyoman; Wardhana, I Made; Winaya, Ketut Kwartantaya (E-Jurnal Medika Udayana, 2023)
Skin cancer is one of the most common cancers found in Indonesia. The most common skin cancers in Indonesia are basal cell carcinoma, squamos cell carcinoma, and melanoma. One of the harms caused by waves of solar radiation is damaging the DNA which later activates oncogene cells that could lead to cancer. One of the livelihoods that are abundant in Indonesia is agriculture. Farmers that are exposed to direct sunlight with excessive intensity are very susceptible to skin cancer which main risk factor is sunlight. The amount of outdoor activities with a superfluity intensity plus ignorance and the incapability to protect oneself from the sun causes the risk of getting skin cancer to be higher. Methods: The study was conducted using a descriptive approach with a transverse study design. Respondents took a total sampling of 64 respondents. Data collection was executed using a self-administered questionnaire instrument. The questionnaire consists of 20 numbers for the level of knowledge and 20 numbers for the attitude. Results: The level of good knowledge about sunlight as a risk factor for skin cancer as many as 45 people (70.31%), sufficient knowledge 17 people (26.56%), lack of knowledge 2 people (3.13%). Attitude about sunlight as a risk factor for skin cancer was 38 people (59.38%), 23 people (35.94%), a bad attitude was 3 people (4.68%). Conclusion: The level of understanding of farmers in Subak Sempidi, Sempidi Village, Mengwi District, Badung Regency regarding sunlight as a risk factor for skin cancer is in a good category.